Growth Rate and Production of Hybrid and Local Maize (Zea Mays L.) in Response to Various Doses of Nitrogen Fertilization - Wirastiti, Ni Ketut; Setiawan, Kukuh; Manik, Tumiar Katarina (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Corn (Zea mays L.) is a strategic commodity after rice so that the productivity need to be optimize through nitrogen fertilization. The aim of this research is to evaluate the effect of various doses of urea fertilizer on the growth rate and yield of hybrid corn and local corn. This research was conducted from June to October 2022 on the pilot land of the Agricultural Training Center (Bapeltan), Hajimena, Bandar Lampung. The factorial experiment (5x2) was arranged in a randomized complete block design with 3 replications. The first factor is urea fertilizer doses, namely: 200 kg/ha (N1), 250 kg/ha (N2), 300 kg/ha (N3), 350 kg/ha (N4) and 400 kg/ha (N5), while other fertilizers were given to all experimental plots in the same rate (150 SP-36 kg/ha and 100 kg KCl kg/ha). The second factor is the corn variety, included V1 (BISI-18) and V2 (Tongkol Merah) varieties. The results showed that increasing dose of urea from 200 to 400 kg/ha was not able to increase the growth rate of both corn varieties. The productivity of the BISI-18 corn variety is higher than that of the Tongkol Merah as indicated by the wet weight of the cobs (g), the dry weight of grains per plot (g), and the yield of corn dry grains (tons/ha). The yield of dry corn seeds for the BISI-18 corn variety was 11.7 tons/ha, while for the Tongkol Merah variety was 9.44 tons/ha. Keywords: Fertilizer dosage, Hybrid corn, Local corn, Nitrogen use efficiency, Yield.